A time series analysis of the effects of financial incentives and mandatory clinical applications as interventions to improve spontaneous adverse drug reaction reporting by hospital medical staff in China. Issue 6 (4th July 2017) - Chang, Feng; Xi, Yue; Zhao, Jie; Zhang, Xiaojian; Lu, Yun
Abstract: Rationale, aims, and objectives: Spontaneous reporting of adverse drug reactions (ADRs) in hospitals is often under‐reported, which may lead to problems in patient management. This study was aimed to assess the effectiveness of a financial intervention based on a fine and a bonus for improving spontaneous reporting of ADRs by physicians in a hospital setting. Methods: This study was conducted at the First Affiliated Hospital of Zhengzhou University (China). Starting in 2009, a bonus of 20 RMB (Chinese currency) was given for each spontaneous ADR report, and a fine of 50 RMB was given for any withheld ADR report. A time series analysis using autoregressive integrated moving average models was performed to assess the changes in the total number of spontaneous ADR reports between the preintervention period (2006‐2008) and during the first (2009‐2011) and second (2012‐2014) intervention periods. Results: The median number of reported ADRs per year increased from 29 (range 27‐72) in the preintervention period to 277 (range 199‐284) in the first intervention period and to 666 in the second (range 644‐691). The monthly number of reported ADRs was stable during the 3 periods: 3.56 ± 3.60/month (95% confidence interval (CI), 2.42‐4.75) during the preintervention period, 21 ± 13/month (95% CI, 16.97‐25.80) in the first intervention period, and 56 ± 20/month (95% CI, 48.81‐62.17) in the second intervention period. Conclusion: A financial incentive and ADR management regulations had a significant effect on the increase of reported ADRs.